The new world order paradigm within the U. S. foreign policy strategy: formation and development - Plashchinsky, Alexander A. (Journal of the Belarusian State University. Sociology, 2019)
The article contains key thesis and results of the long-term research undertaken by the author with regard to the new world order paradigm, that is the wide scale historical and geopolitical project implemented by the «Anglo-American establishment» as well as one of the possible blueprints for the future system of international relations. Threats and risks which have been caused by the implementation of that project are considered. The analysis of the process of formation and development of the liberal paradigm is necessary for further conceptual elaboration of the national idea of the Republic of Belarus.